Sistem Pendukung Keputusan dengan Metode Multi Factor Evaluation Process dalam Mengidentifikasi Penerima Bantuan yang Tepat pada Program Keluarga Harapan - Sutra, Lidia; Nurcahyo, Gunadi Widi (Jurnal Informatika Ekonomi Bisnis, 2021)
The Family Hope Program (PKH) is a conditional cash transfer program for poor families. PKH is one of the government programs in reducing poverty in Indonesia. The large amount of PKH participant data that will be processed can take a lot of time and can hamper the flow of aid. This study aims to create a system that can assist PKH facilitators in identifying the right beneficiaries for the PKH program quickly and with accurate results. The method used in this research is the Multi Factor Evaluation Process (MFEP) method. The data processed in this study consisted of 25 PKH participant data obtained from PKH Nagari Kunangan Parik Rantang facilitators. The criteria used as an assessment for PKH participants were having early age children, pregnant women, the elderly, with disabilities, high school children, junior high school children, and elementary school children. The stages of the MFEP method are determining the weight of each criterion, filling in the value for each factor, and calculating the evaluation weight then adding up all the evaluation weights to get the total evaluation value which is used as the final value in decision making. From data processing on 25 PKH participants, the results of the eligible decisions consisted of 20 participants and 5 non-eligible participants. The data that has been processed using the MFEP method is compared with data from PKH Facilitators and produces decisions with a 100% similarity level. With this level of accuracy, the MFEP method can be used in identifying the right recipients of assistance in the Family Hope Program.